The Brooklyn Cyclones : Hardball Dreams and the New Coney Island. - Osborne, Ben (NYU Press, 2004)
When professional baseball returned to Brooklyn in 2001, fans were jubilant and the media swarmed. After losing the Brooklyn Dodgers to California 44 years ago, Brooklyn baseball fans could once again claim a team of their own: the Cyclones, a Class A affiliate of the New York Mets. The Brooklyn Cyclones: Hardball Dreams and the New Coney Island recounts that first season of the Cyclones. From the construction of the incredible Keyspan Park at Coney Island to their improbable successes on the field, Ben Osborne tells the story of the Cyclones' delicate first year of operation. We see the story.